2011
DOI: 10.3928/1081597x-20101210-01
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure During Corneal Flap Preparation: Comparison Among Four Femtosecond Lasers in Porcine Eyes

Abstract: There is considerable variation in IOP among the tested femtosecond lasers during a regular lamellar flap creation and during the worst-case procedure. The VisuMax femtosecond laser seems to cause the lowest IOP rise in both settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 21 publications
4
49
1
5
Order By: Relevance
“…All treatments were performed as bilateral simultaneous LASIK using the Visumax femtosecond laser [15][16][17][18] and the MEL 80 excimer laser. 13 A nomogram based on previous treatments was used to calculate the laser data entry; both surgeons used the same nomogram.…”
Section: Methodsmentioning
confidence: 99%
“…All treatments were performed as bilateral simultaneous LASIK using the Visumax femtosecond laser [15][16][17][18] and the MEL 80 excimer laser. 13 A nomogram based on previous treatments was used to calculate the laser data entry; both surgeons used the same nomogram.…”
Section: Methodsmentioning
confidence: 99%
“…In all studies published so far, resulting IOP values were often determined for single steps of a specific surgical procedure [1,11,28], and the authors observed a strong surgeon-dependent correlation. Christensen et al [27] investigated the IOP resulting from insertions of 19-to 32-G needles and referenced the applied force.…”
Section: Discussionmentioning
confidence: 99%
“…IOP rises up to 300 mm Hg and higher during some stages of surgery [1,11]. The IOP reaches especially high values during the cutting stages [1,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massive IOP rises as seen in porcine eyes while using flat applanation interfaces (for a refractive procedure, not for cataract extraction) in the range between 130 and 180 mm Hg seem to pose a significant risk for those elderly patients with glaucoma as a comorbidity. Even curved applanation interfaces were associated with massive IOP rises between 65 and 205 mmHg [7]. A fluid-filled interface has been proven to lead only to comparably small IOP increases for a short time.…”
Section: Iop During Femtosecond Laser-assisted Cataract Surgerymentioning
confidence: 99%